Performance analysis and optimization of a novel high-efficiency flower-inspired solar still. (1st January 2022) - Zhao, Yunsheng; Ramadan, Omar; Kong, Hui; Xue, Xiaodi; Riffat, Saffa; Zheng, Hongfei
Graphical abstract: Highlight: A novel high-efficiency flower-inspired solar still was developed. The light-concentrating characteristics of flower are presented. Optimization methods of the corolla-shaped concentrator are presented. Modelling and optimization methods of the system are studied respectively. The theoretical water yield and efficiency can reach 6.5 kg/(m 2 ·h) and 480%. Abstract: Solar still provides a potential solution to water shortage in rural areas. However, due to large optical and thermal losses, solar still system suffers from low energy efficiency (30%∼45%). This work aims to present a novel high-efficiency multi-stage floating flower-inspired solar still. To improve the optical performance of the new system, a corolla-shaped concentrator matching the system is designed and optimized through optical simulation. The heat and mass transfer models of the single-stage and multi-stage system were established and validated to study and optimize the performance. The optical simulation result of the corolla-shaped concentrator shows that its light receiving rate is higher than 0.75 with incident angle of 20°. The performance simulation results demonstrate that the water yield rate and the total energy efficiency of the single-stage flower-inspired solar still are 0.85 kg/(m 2 ·h) and 65%, respectively. While the water yield rate and the total energy efficiency of the seven-stage system can reach about 6.5 kg/(m 2 ·h) and 480%, which is 10.66 times higher than the energy efficiency of the conventional solar still system (45%). Furthermore, the economic analysis shows that the cost and the payback period of the seven-stage system are 0.001$/L and 0.25 years, respectively. Therefore, the proposed novel solar desalination system with high efficiency and low cost greatly improves application of solar still in rural areas.